The Adenomyosis and infertility - underestimated challenge in reproductive medicine - Znamirowska, Katarzyna; Bukała, Martyna; Ochyra, Karolina; Pudło, Kornelia; Frydrych, Jowita; Prucnal, Gabriela; Ryba, Karolina; Zacher, Klaudia; Walkiewicz, Patrycja; Rakoczy, Anna (Quality in Sport, 2025)
Introduction: Adenomyosis is considered as a chronic gynecological condition increasingly observed among women of reproductive age. It remains underdiagnosed and frequently underestimated as a contributing factor in fertility disorders. Characterized by the presence of endometrial glands and stroma within the myometrium, adenomyosis causes progressive structural and functional uterine changes that may impair endometrial receptivity and disrupt implantation. Aim of the study: This review aims to summarize current knowledge on the effects of adenomyosis on fertility. It focuses on the pathophysiological mechanisms involved, diagnostic tools, classification systems.. It explores the pathophysiological mechanisms that contribute to impaired reproductive outcomes, as well as available diagnostic methods that enable an effective identification of the condition. Materials and methodology:The literature review includes articles from databases (PubMed), selected to their citation, using keywords “adenomyosis”, “infertility” Conclusion: Adenomyosis is increasingly recognized as a potential contributing factor to female infertility. Anatomical and functional alterations within the uterus may impair embryo implantation and early pregnancy development. Current evidence highlights the importance of including adenomyosis in the diagnostic work-up and management of infertile patients. A deeper understanding of its underlying mechanisms may lead to more effective and individualized treatment strategies.